Inovasi Lembar Kerja Siswa Reaksi Redoks Berbasis Pemecahan Masalah Untuk Siswa SMA - Ramlan Silaban; Marianna Pasaribu; Sary MF Sitompul; Trisna W Simanullang (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract. This study aimed to obtain an innovative student worksheet (LKS) on Redox reaction and its influence on learning outcomes, affective and psychomotor attitudes of high school students. To achieve the objectives, conducted quasi-experimental research which starts from the assessment of some chemical LKS redox which  used in high school students of MIA of X class, compile worksheets based innovative PBL, standardize, and limited test. There are two types of instruments in this research instrument a questionnaire BSNP non test and test instrument in the form of a multiple choice test is valid. The results obtained from this study: (1). Student worksheet (LKS) redox developed already meet the standards set by the National Education Standards Beureau. (2) The results of the student learning outcomes of senior high school students that learned using innovative worksheets on the redox reaction is higher than using an existing worksheet. (3). Affective percentage of students that learned using innovative worksheets on the redox reaction is higher than using existing worksheets. (4). Psychomotor percentage of students that learned using innovative worksheets on the material and the redox reaction is higher than using existing worksheets. Kata kunci: LKS inovatif, problem based learning, reaksi oksidasi dan reduksi